(Re) visitando a teoria de valor: análise da produção acadêmica sobre a teoria do valor na base de dados Scopus - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia/Universidade Federal do Rio de Janeiro, 2019)
This research studies the scientific production on the value theory of Karl Marx’s published indexed in Scopus database. It presents the main categories theory of value, approaching its concepts and definitions and tracing the interlocution with Information Science. It presents an exposition of the concepts of immaterial labor, cognitive capitalism and informational work. In general, it analyzes the scientific production on the theory of value, in terms of the articles published in journals, indexed in Scopus database specifically aiming to map this production and the words network. Based on the hypothesis that the basic categories of theory of value are widely used and reinforce the conjecture that this theory is used is to confront ideas of generation, accumulation, appropriation of wealth and value. It is a qualiquantitative research, with a descriptive approach. It uses information retrieval and retrieval protocols as an instrument for collecting data. It adopts as methodology of data analysis the bibliometric method of word co-occurrence. The results signal to a concentration of scientific production in developed countries, the main journal for sharing this knowledge is Cambridge Journal of Economics, linked to Oxford University. The maps of co-occurrence of words register a high presence of the terms Marx, Marxism, economic theory, value. It is concluded that this study allowed to know the panorama of the scientific production on Karl Marx’s theory of value and its nuances of research from the production indexed in Scopus database.
Keywords: Ciência da Informação; Teoria do valor; Karl Marx; Estudos bibliométricos; Information Science; Theory of value; Bibliometric studies; Ciência da informação